AN ANALYSIS OF PERSONIFICATION IN THE SOME SELECTED POEMS BY ROBERT FROST - Vinsensia Nidi; Ni Made Verayanti Utami; Putu Devi Maharani (ID Solutions, 2022)
This study aims to determine the type of personification figure of speech and the general meaning of personification in Robert Frost’s selected poems entitled (Leave Compared With Flowers, The Road Not Taken, Stopping By Woods On A Snow Evening, Christmas Tree, Pan With Us, The Tuft of Flowers, The Trial by Existence, The Generation Of Men, Home Burial, O Erathward, Wind and Window Flower, Bond and Free, and Spoils of The Dead. Based on the use of personification figure of speech in Robert Frost’s poetry, the researcher knows the most dominant type of personification. Personification figure of speech has 2 types, namely prosopographia and prosopopopeia. The data of this research are documents from some selected poems by Robert Frost’s poems. In this study, the researcher used document analysis as a method and technique of data analysis. From the results of the study, researchers found 24 personifications. Then the researcher concludes that from the two types of personification figure of speech found in Frost’s poems, there are 6 prosopographia and 18 prosopopopeia. From this data, it can be seen that the dominant type used is prosopopopeia.